2019
DOI: 10.3389/fpsyg.2019.00286
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity and Mental Health: The Moderating Role of Coping Strategies From a Gender Perspective

Abstract: Job insecurity is a growing phenomenon, typical of an employment context characterised by high rates of temporary work and unemployment. Previous research has shown a direct relationship between job insecurity and mental health impairment. The present analysis goes into this relationship in depth, studying the moderating role of coping strategies and predicting that men and women implement different types of strategies. A sample of 1.008 workers is analysed, 588 women and 420 men. The Tobin CSI scale was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 60 publications
(88 reference statements)
9
54
0
1
Order By: Relevance
“…It has also been found that women use this social resource more often and more efficiently than men [50]. These results were confirmed in a recent study [51] that showed when women actively resort to their social support network, this acts as a buffer for the negative consequences of job insecurity. These conclusions agree with those proposed by [48] that the effectiveness of this interpersonal-social resource depends on it serving specifically to manage the stressful situation.…”
Section: Threat and Mental Healthsupporting
confidence: 65%
“…It has also been found that women use this social resource more often and more efficiently than men [50]. These results were confirmed in a recent study [51] that showed when women actively resort to their social support network, this acts as a buffer for the negative consequences of job insecurity. These conclusions agree with those proposed by [48] that the effectiveness of this interpersonal-social resource depends on it serving specifically to manage the stressful situation.…”
Section: Threat and Mental Healthsupporting
confidence: 65%
“…The findings of this study, which prove a significant association between perceived job insecurity and anxiety in the European labor force, confirm research in the field documenting that women seem to react negatively, and in the same way as men do, to adverse work and employment conditions (Pelfrene et al, 2003;László et al, 2010;Buffel et al, 2015;Reichert and Tauchmann, 2017;Menéndez-Espina et al, 2019). The magnitude of the association between job security and anxiety may be regarded as moderate and such result is also consistent with previous evidence (László et al, 2010;Buffel et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Studying gender as a moderator is important because, while both men and women are likely to experience some level of job insecurity, gendered societal expectations and work‐related identity (Mauno & Kinnunen, 2002) and gender‐specific coping mechanism (Menéndez‐Espina et al, 2019) may lead to a different relationship between job insecurity, negative work‐to‐family spillover (hereafter referred to as negative work spillover) and sleep quality among men and women. Past research on the role of gender in the relationship of job insecurity and individual and work outcomes has demonstrated mixed findings, with the vast majority of research concluding that there is a greater sensitivity to job insecurity among men than among women (e.g., De Witte, 1999; Ferrie, Shipley, Stansfeld, & Marmot, 2002; Levenstein et al, 2001; Richter, 2011).…”
Section: The Moderating Role Of Gendermentioning
confidence: 99%